A rare case report of vulval fibroadenoma - Ilayappan, Saranya Sri; Sivarajan, Sujitha; Vijayakrishnan, Mala; Priyadharshini, Sarah Grace (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Vulval fibroadenoma is an extremely rare entity seen in women of the age group 20-80 years. Only 50 cases of ectopic benign mammary tissue have been reported in medical literature, with vulva being the second most common extra-mammary site. We report a case of a 44 years old female, para 2 live 2, who presented with an initially endophytic swelling in her vulva for 6-7 months, which became exophytic since 2 months, associated with pain for 1 month and purulent discharge since 2 days. On examination, a 4×2 cm fleshy exophytic mass with a cauliflower-like appearance was noted on the right labia majora, just below labia minora with no active purulent discharge. Based on the clinical examination, our differential diagnosis included condyloma accuminata, infected sebaceous cyst, hidradenoma papilliferum, apocrine adenoma, Bartholin’s cyst and phyllodes tumour. A surface biopsy and cytology taken from the growth was suggestive of infected Bartholin’s cyst. Pus culture showed no growth. She underwent excisional biopsy subsequently with 2 mm margin clearance. Histopathology was reported as vulval fibroadenoma with stromal cellularity. A unique feature of our case is that an initially endophytic mass became exophytic with purulent discharge unlike many other reported cases worldwide. A surface biopsy is a useful tool to arrive at a preoperative diagnosis. Surgical excision with a clear and safe margin is recommended to avoid recurrence. If malignancy is reported in histopathology, testing for hormone receptors can be helpful. Women have to be generally more aware about such abnormal lesions and should report immediately.